Legal Gaps in Personal Data Protection: Reforming Indonesia’s Population Administration Law - Triyanti, Ninuk; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego (Faculty of Law, Hasanuddin University, 2025)
This study critically examines the existing legal framework for personal data protection within Indonesia’s population administration system. Through a normative legal research approach, it identifies significant regulatory gaps that leave personal information vulnerable to misuse and breaches. The results show that the current legal policies remain insufficient, as numerous aspects of personal data protection have yet to be explicitly regulated in the Population Administration Law. Despite the enactment of a national personal data protection law, its effectiveness is undermined by the lack of comprehensive integration into the Population Administration Law. This research proposes reconstructing the legal framework to address essential aspects of data management—such as collection, utilization, safeguarding, exchange, and misuse prevention—while establishing clear access rights, prohibitions on unauthorized activities, and a structured system of proportional sanctions. By incorporating specialized legal provisions and aligning with international best practices, these reforms would strengthen Indonesia’s data protection framework, enhance public trust, and reinforce the government’s role in safeguarding citizens’ personal information.